Traditional Chinese Medicine in Treating Children With Coronavirus Disease 2019: A Scoping Review - Duan, Naifan; Liu, Bin; Li, Xiaona; Xiong, Yibai; Li, Li; Ma, Yan; Lu, Cheng (Frontiers in Pediatrics, 2022)
Coronavirus Disease 2019 (COVID-19) is currently widely spread across the world. Traditional Chinese Medicine (TCM) plays an important role in the overall treatment process. As a special group of the population, the treatment outcome of COVID-19 children has attracted much attention. Our study summarizes the current situation of TCM treatment of COVID-19 children. The results showed that TCM displayed a positive role in the treatment process, and no significant adverse reactions were found. Our findings provide analytical evidence for the efficacy and safety of TCM participation in the treatment of COVID-19 in children.